Septic Arthritis: The drainage controversy - de Jong PH; Bisoendial RJ; Lems WF (Rheumatica Acta: Open Access - Peertechz Publications, 2018)
Objective: Septic arthritis is a relatively rare disease, which is associated with a high morbidity and mortality. Treatment consists of prolonged antibiotic therapy and removal of intra-articular inflammatory debris. However, there is much controversy about the most effective drainage method. Therefore, we compared the clinical efficacy of (daily) needle aspiration with surgical drainage in adult patients with septic arthritis. Methods: In this systemic review, all articles describing treatment outcomes based upon the drainage method were retrieved. We also performed a meta-analysis, irrespective of the clinical or methodological heterogeneity. Results: We included 5 studies, all retrospective in nature, and if combined, with a total number of 450 patients. These studies showed that complete rehabilitation occurred more often in septic arthritis patients treated with needle aspirations (67-76%) compared to surgically treated patients (32-56%). The pooled relative risk (RR) (95% confidence interval (CI)) for complete rehabilitation in needle aspirations compared to surgical drainage was 1.46 (1.22-1.75). On the other hand, the mortality rate was slightly higher in the daily aspiration group (respectively 3-13% versus 2.5-5%). The pooled RR (95% CI) for mortality in needle aspiration versus surgical treatment was 2.23 (0.84-5.91). Noteworthy is the fact that serious underlying illnesses were more frequent in the needle aspiration group.  Conclusion: We recommend (daily) needle aspirations as initial method of drainage in patients with an uncomplicated septic arthritis, except for following more complex/difficult situations, in which surgical drainage is preferred: (1) inaccessible joints; (2) unsatisfactory clinical response; and (3) inability to aspirate the joint dry.